Assessment of functional diversities in patients with Asthma, COPD, Asthma-COPD overlap, and Cystic Fibrosis (CF) - Kraemer, Richard; Baty, Florent; Smith, Hans-Jürgen; Minder, Stefan; Gallati, Sabina; Brutsche, Martin H.; Matthys, Heinrich (PloS one, 2024)
The objectives of the present study were to evaluate the discriminating power of spirometric and plethysmographic lung function parameters to differenciate the diagnosis of asthma, ACO, COPD, and to define functional characteristics for more precise classification of obstructive lung diseases. From the databases of 4 centers, a total of 756 lung function tests (194 healthy subjects, 175 with asthma, 71 with ACO, 78 with COPD and 238 with CF) were collected, and gradients among combinations of target parameters from spirometry (forced expiratory volume one second: FEV 1 ; FEV 1 /forced vital capacity: FEV 1 /FVC; forced expiratory flow between 25–75% FVC: FEF 25-75 ), and plethysmography (effective, resistive airway resistance: sR eff ; aerodynamic work of breathing at rest: sWOB), separately for in- and expiration (sR eff IN , sR eff EX , sWOB in , sWOB ex ) as well as static lung volumes (total lung capacity: TLC; functional residual capacity: FRC pleth ; residual volume: RV), the control of breathing (mouth occlusion pressure: P 0.1 ; mean inspiratory flow: V T /T I ; the inspiratory to total time ratio: T I /T tot ) and the inspiratory impedance (Z in pleth = P 0.1 /V T /T I ) were explored. Linear discriminant analyses (LDA) were applied to identify discriminant functions and classification rules using recursive partitioning decision trees. LDA showed a high classification accuracy (sensitivity and specificity > 90%) for healthy subjects, COPD and CF. The accuracy dropped for asthma (~70%) and even more for ACO (~60%). The decision tree revealed that P 0.1 , sR tot , and V T /T I differentiate most between healthy and asthma (68.9%), COPD (82.1%), and CF (60.6%). Moreover, using sWOB ex and Z in pleth ACO can be discriminated from asthma and COPD (60%). Thus, the functional complexity of obstructive lung diseases can be understood, if specific spirometric and plethysmographic parameters are used. Moreover, the newly described parameters of airway dynamics and the central control of breathing including Z in pleth may well serve as promising functional marker in the field of precision medicine.